2003
DOI: 10.1002/elan.200390043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Incorporated Lipophilic Particles on Ion Fluxes Through Polymeric Ion‐Selective Membranes

Abstract: The incorporation of lipophilic particles into the sensing membrane of ion-selective electrodes (ISEs) can strongly influence the uptake of ions from the sample. The apparent super-Nernstian response of ISEs caused by a strong flux of primary ions from the sample to the inner solution can be suppressed completely. This opens up new possibilities of improving the ruggedness of trace-level measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…Moreover, superNernstian potential jumps are typically observed at concentrations at or below 1 × 10 −6 M, suggesting that the super-Nernstian response observed here may be caused by a different phenomenon. The Pretsch group has studied the influence of lipophilic silica gel particles on trans-membrane ion fluxes that occur in ISE membranes [28]. They concluded that a super-Nernstian electrode response could be eliminated if the ion-selective membrane was inverted, so that the particle layer was located on the sample side of the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, superNernstian potential jumps are typically observed at concentrations at or below 1 × 10 −6 M, suggesting that the super-Nernstian response observed here may be caused by a different phenomenon. The Pretsch group has studied the influence of lipophilic silica gel particles on trans-membrane ion fluxes that occur in ISE membranes [28]. They concluded that a super-Nernstian electrode response could be eliminated if the ion-selective membrane was inverted, so that the particle layer was located on the sample side of the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Another method of reducing transmembrane ion fluxes made use of lipophilic silica gel particles of 15 -35 mm diameter added to the membrane matrix [54]. It was shown that the apparent super-Nernstian response of ISEs caused by a strong flux of primary ions from the sample to the inner solution can be suppressed completely (see Fig.…”
Section: Suppressing Ion Fluxes In the Membranementioning
confidence: 99%
“…Normally, the diffusion coefficients in the aqueous phase may not be increased. Recently, a lowering of the LOD that was independent of the composition of the inner solution was also achieved by partially blocking the sample side of the membrane by using inert lipophilic microparticles that were embedded during membrane construction [21].…”
Section: Polymeric Membrane Potentiometric Sensors With Aqueous Innermentioning
confidence: 99%